Investigation of Reasons for Non-completion of Specific Health Guidance Program - Hyodo, Sachie; Satou, Noriko; Itou, Takashi; Goto, Mariko; Suwa, Ryoko; Takagi, Junko (Official Journal of Japan Society of Ningen Dock, 2012)
Objective: In Specific Health Guidance, it may not be possible to provide continuous follow-up up to the final guidance session for various reasons. The reasons for high non-completion rates for Specific Health Guidance at other facilities and the factors behind non-completion were unclear. Our objective was therefore to investigate the reasons for persons not completing Specific Health Guidance at Seirei Numazu Hospital and to determine effective methods for continuous follow-up. Methods: Among 12 persons conducting Specific Health Guidance at Seirei Numazu Hospital, we conducted group interviews of 6 who were in charge of 17 persons who did not complete Specific Health Guidance in fiscal 2009, and performed qualitative analysis of the findings. Results: The analysis of 171 code items enabled us to determine the causes of non-completion and effective methods for continuous follow-up. Conclusion: The findings suggested that the factors behind non-completion were those related to the persons receiving guidance (hereafter subjects) and those related to the persons in charge of guidance and the operation of the facility giving it. We determined that there were 2 effective ways of ensuring continuous follow up which were enhancement of guidance techniques and refinement of follow-up procedures. Listening to the opinions of the persons in charge of guidance provided a good opportunity to consider the causes of non-completion, effective ways for ensuring continuous support and factors interfering with follow-up. However, due to the small number of subjects and the fact that opinions were those of persons in charge of guidance rather than those not completing it, there is a potential bias in the results. We aim to study the issue of non-completion further in the future.